The parasitic life-cycle of Haemonchus similis - Bianchin, Ivo; Melo, Hermano J.H. de; Gomes, Alberto (Pesquisa Agropecuaria Brasileira, 2014)
The parasitic life-cycle of Haemonchus similis (Travassos 1914) is described for the first time and compared with those of H. contortus (Rudolphi 1803) and H. placei (Place 1893). Fourteen Nelore calves five to six years of age, made worm-free by application of large spectrum anthelmintics, were inoculated with 10,000 infective larvae of H. similis and slaughtered at intervals of 36, 48, 76 hr, and 5, 8, 10, 13, 15, 18, 21, 24 and 28 days after infection. The remaining two calves were left in order to verify the prepatent period. The dynamics of infection was the following: 36/48 hr, exsheathed third-stage larvae; 76 hr., initial 4th stage larvae; 8th day, final 4th stage larvae; 18th day, 5th stage larvae and 28th day, adult helminths. The prepatent period was of 27/28 days. The congestion of the abomasum mucosa was very high until the 13th day, whereas the oedema increased until the last necropsy. The majority of immature forms were recovered from the digested material until the 5th day, indicating a short histotrophic phase. It was observed that the parasitic life-cycle of H. similis is similar to that of H. placei, but differed to that of H. contortus with respect to prepatent period and the rate of development of some stages. The morphology of the different stages, except the adult phase, is similar to the other Haemonchus species of cattle.